Eruption [compact disc, unabridged] : the untold story of Mount St. Helens - Olson, Steve, 1956- (HighBridge Audio, 2016)
For months in early 1980, scientists, journalists, and ordinary people listened anxiously to rumblings in the longquiescent volcano Mount St. Helens. Still, when a massive explosion took the top off the mountain, no one was prepared. Fifty-seven people died, including newlywed logger John Killian (for years afterward, his father searched for him in the ash), scientist Dave Johnston, and celebrated local curmudgeon Harry Truman. The lives of many others were forever changed.